DETECTING STATISTICAL INTERACTION BETWEEN SOMATIC MUTATIONAL EVENTS AND GERMLINE VARIATION FROM NEXT-GENERATION SEQUENCE DATA - HU, HAO (2014)
The two-hit model of carcinogenesis provides a valuable framework for understanding the role of DNA repair and tumor suppressor genes in cancer development and progression. Under this model, tumor development can initiate from a single somatic mutation in individuals that inherit an inactivating germline variant. Although the two-hit model can be an overgeneralization, the tendency for the pattern of somatic mutations to differ in cancer patients that inherit predisposition alleles is a signal that can be used to identify and validate germline susceptibility variants. Here, we present the Somatic-Germline Interaction (SGI) tool, which is designed to identify statistical interaction between germline variants and somatic mutational events from next-generation sequence data. SGI interfaces with rare-variant association tests and variant classifiers to identify candidate germline susceptibility variants from case-control sequencing data. SGI then analyzes tumor-normal pair next-generation sequence data to evaluate evidence for somatic-germline interaction in each gene or pathway using two tests: the Allelic Imbalance Rank Sum (AIRS) test and the Somatic Mutation Interaction Test (SMIT). AIRS tests for preferential allelic imbalance to evaluate whether somatic mutational events tend to amplify candidate germline variants. SMIT evaluates whether somatic point mutations and small indels occur more or less frequently than expected in the presence of candidate germline variants. Both AIRS and SMIT control for heterogeneity in the mutational process resulting from regional variation in mutation rates and inter-sample variation in background mutation rates. The SGI test combines AIRS and SMIT to provide a single, unified measure of statistical interaction between somatic mutational events and germline variation. We show that the tests implemented in SGI have high power with relatively modest sample sizes in a wide variety of scenarios. We demonstrate the utility of SGI to increase the power of rare variant association studies in cancer and to validate the potential role in cancer causation of germline susceptibility variants.